Enhanced performance of T2SLs LWIR avalanche photodiodes with a separate AlxGa1-xSb multiplication layer - Chen Liu; Haifeng Ye; Weilin Zhao; Rong Bai; Yanli Shi (Scientific Reports)
Abstract Detector research is rapidly advancing to meet the growing demands for long-wavelength infrared (LWIR) detectors in applications such as deep space exploration, medical imaging, meteorological detection, and thermal imaging. In this study, we propose a high-performance Type-II superlattices (T2SLs) long-wavelength infrared (LWIR) avalanche photodiode (APD) with a separate absorption and multiplication (SAM) structure. Compared to conventional LWIR detectors, this device achieves over a 100-fold increase in responsivity at 77 K. This advancement is attributed to the design of a separate multiplication layer with the wide bandgap material AlxGa1-xSb in the InAs/GaSb T2SLs LWIR APD, which suppresses the electric field in the absorption layer while maintaining high gain. Using computer-aided design technology, we analyzed the internal electric field values and IV characteristics under key layer parameters. Simulation results indicate that under 12 μm monochromatic light irradiation at 77 K, the device can achieve a responsivity exceeding 200 A/W. These features are comparable to the most advanced band-structure-engineered high-gain LWIR photodetectors based on Type-II superlattices. This structural design concept provides a practical and feasible approach to achieving high-performance T2SLs LWIR infrared detectors.